2023
DOI: 10.1111/cas.15886
|View full text |Cite
|
Sign up to set email alerts
|

N6‐methyladenosine‐modified FAM111A‐DT promotes hepatocellular carcinoma growth via epigenetically activating FAM111A

Abstract: As an epitranscriptomic modulation manner, N6‐methyladenosine (m6A) modification plays important roles in various diseases, including hepatocellular carcinoma (HCC). m6A modification affects the fate of RNAs. The potential contributions of m6A to the functions of RNA still need further investigation. In this study, we identified long noncoding RNA FAM111A‐DT as an m6A‐modified RNA and confirmed three m6A sites on FAM111A‐DT. The m6A modification level of FAM111A‐DT was increased in HCC tissues and cell lines, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Therefore, future studies are required to validate these hypotheses. Recently, long noncoding RNA (lncRNA) of FAM111A (known as FAM111A-divergent transcript or FAM111A-DT) have been shown to promote the progression and poor survival rate of hepatocellular carcinoma (HCC) through its modification by N 6 -methyladenosine (m 6 A) [ 37 ]. The m6A-modified FAM111DT was shown to drive the overexpression of wild-type FAM111A by activating the FAM111A promoter through interaction with the m6A-binding protein YTHDC1 and the recruitment of the histone demethylase KDM3B to FAM111A promoter.…”
Section: Dysregulation Of Fam111 Proteases In Genetic Diseases Includ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, future studies are required to validate these hypotheses. Recently, long noncoding RNA (lncRNA) of FAM111A (known as FAM111A-divergent transcript or FAM111A-DT) have been shown to promote the progression and poor survival rate of hepatocellular carcinoma (HCC) through its modification by N 6 -methyladenosine (m 6 A) [ 37 ]. The m6A-modified FAM111DT was shown to drive the overexpression of wild-type FAM111A by activating the FAM111A promoter through interaction with the m6A-binding protein YTHDC1 and the recruitment of the histone demethylase KDM3B to FAM111A promoter.…”
Section: Dysregulation Of Fam111 Proteases In Genetic Diseases Includ...mentioning
confidence: 99%
“…The m6A-modified FAM111DT was shown to drive the overexpression of wild-type FAM111A by activating the FAM111A promoter through interaction with the m6A-binding protein YTHDC1 and the recruitment of the histone demethylase KDM3B to FAM111A promoter. Furthermore, this study showed that m6A-modified FAM111A-DT promoted HCC cellular proliferation, DNA replication and tumor growth, and mutation of m6A sites on FAM111A-DT abolished these roles [ 37 ] and could represent a viable treatment target for HCC. Additionally, other studies have associated FAM111A variants with prostate cancer predisposition [ 38 ], a novel prognostic and immunologic biomarker for diffuse lower-grade glioma [ 39 ] and early diagnostic indicator of gastric cancer [ 40 ], thus highlighting its essential role in the diagnosis and treatment of cancers.…”
Section: Dysregulation Of Fam111 Proteases In Genetic Diseases Includ...mentioning
confidence: 99%
“…YTHDF2 upregulates LncAY in HCC, and through promoting BMI1 expression, lncAY activates Wnt/β-catenin signaling (Chen et al, 2021b). Increased m 6 A modifications on the lncRNA FAM111A-DT further HCC progression by promoting FAM111A transcription through interactions with YTHDC1 (Pu et al, 2023). ALKBH5 is generally downregulated in HCC, and decreased demethylation of LINC01468 increased its expression, driving NAFLD-HCC progression through CUL4Alinked degradation of SHIP2 and subsequent activation of the PI3K/AKT/mTOR signaling pathway (Wang et al, 2022b).…”
Section: Non-coding Rnasmentioning
confidence: 99%
“…KDM3B is recruited by N 6 -methyladenosine (m 6 A) reader, YTHDC1, to m 6 A-associated chromatin regions. Recruited KDM3B contributes to HCC progression by removing H3K9me2 on the promoter of FAM111A [ 34 , 35 ]. FAM111A, a single-stranded DNA-binding serine protease that promotes DNA synthesis, is reported to be increased in HCC and correlates with poor survival of HCC patients.…”
Section: The Role Of Kdm3b In Tumorigenesismentioning
confidence: 99%